Is there a possibility of perovskite taking over the solar technology market by 2030? - O.Fashina, Adebayo (International Journal of Physical Research, 2019)
In recent time, there have been enormous advances in the development of perovskite solar cells in terms of its efficiency, rising from 3.8 percent in 2009 to 23.7 percent in 2018. This took other solar technologies over thirty years of research to accomplish. On the other hand, perovskite proffers a more affordable solution since it is potentially much cheaper to produce and relatively simple to manufacture than silicon solar cells. In spite of this great potential, perovskite solar cell technology is still in the premature stages of commercialization due to a number of concerns. Moreover, like with many new technologies, there is a difference between what works in the laboratory at small-scale and in the factory at large-scale. Thus, looking at perovskites as a material, it has the tendency to be a bit unstable at high temperature and susceptible to moisture and these could cause the decomposition of cells. The question here is: can perovskite outshine silicon solar cel1s in the next 10 years considering the successes so far and the vigorous research that is presently taking place globally?Â Â